Suburban farmers’ perception about urban sprawl on livelihoods and environment in Ethiopia: Evidence from Sheger City Administration - Faris Edris Lemma; Paulos Gutema Negeri; Jonse Bane Boka (Environmental Challenges)
Urban sprawl is a global phenomenon which is becoming a serious challenge for suburban farm households’ lives and livelihoods. This study was conducted to assess the perception of suburban farmers about urban sprawl in Sheger City, Ethiopia. The research utilized survey data from 393 households selected by multistage sampling and Focus Group Discussion, Key Informant Interviews, and field observation. Two outcome variables were developed from a total of 11 Likert scale items representing socioeconomic and socioenvironmental impacts of urban sprawl. Selected sociodemographic and environmental impact variables were used as predictor variables. Perception indices were computed for each outcome variable for each respondent. Descriptive statistics and ordered logistic regression were employed for the data analysis. Awareness of respondents particularly women about urban expansion and its consequences is noticeably high. 82.4% & 82.5% responded “Agree” to the outcome variables items respectively. Among others, land proximity to main road, land expropriation status, and education were major determinants with their 6.8%, 6.5%, & 1.9% respective probabilities of shaping households’ perception when the two outcome variables are combined. Agriculture and hence land is still a primary source of livelihood for over 70% of the households. The youth is evacuating the sector as the mean age of respondents is closer to retirement. Pre-emptive informal land selling to escape expropriation is escalating urban sprawl in the area. Therefore, inclusive and participatory market-based temporal land valuation, agricultural intensification, and fair compensation were recommended in implementing inclusive, planned and sustainable urbanization.